miR-330-3p suppresses liver cancer cell migration by targeting MAP2K1 - Jin, Zhe (Oncol Lett, 2019)
MicroRNAs, considered as a promising focus for the treatment of tumors, are key regulators of a large number of genes. The aim of the present study was to investigate the biological functions of microRNA (miR)-330-3p in liver cancer as it had been identified previously that miR-330-3p was deregulated in liver cancer. In order to identify the function of miR-330-3p in liver cancer, the expression of miR-330-3p was determined in liver cancer tissues and adjacent non-tumor tissues using reverse transcription-quantitative polymerase chain reaction analysis. To elucidate the function of miR-330-3p in liver cancer, miR-330-3p was overexpressed using mimic transfection. Cell migration was inhibited by miR-330-3p in liver cancer cells. The miRNA target prediction databases were used to identify potential target genes of miR-330-3p in liver cancer. The RNA level of mitogen-activated protein kinase kinase 1 (MAP2K1) was downregulated by miR-330-3p in liver cancer cells. In conclusion, miR-330-3p suppresses cell migration by targeting MAP2K1 in liver cancer cells.